Research and Its Importance - Syed Shoeb Ahmad (The Ophthalmology, 2015)
Research has been defined as a “systematic investigation, including research developments, testing and evaluation, designed to develop or contribute to generalizable knowledge”. It also aims to establish facts and reach new conclusions. The Cambridge English dictionary defines research as a “detailed study of a subject, especially in order to discover (new) information or reach a (new) understanding”. However, research often goes beyond the subject, going from the sub-molecular level to the study of gigantic structures, in order to develop new ideas, confirm or reject old theories and search for hypotheses. The basic tenet of research includes the gathering of data, information and observations to advance our knowledge. The evolution of the human race and technological advancement seen over the last couple of decades is a direct consequence of our increasing interest and dependence on research. While the human race is estimated to be 200,000 years old, most of our progress has occurred in the last 10.000 years. This advancement can be attributed to a better understanding of research methodologies.